Registro de produtos biológicos no Brasil e nos principais órgãos regulatórios internacionais: desafios e oportunidades de melhorias para a regulamentação brasileira - Marin, Sara Rico Bocato (2021)
Biological products, originated through the new biotechnological route of synthesis, offer options towards personalized medicine and targeted therapy. The inherent complexity of biological medicines poses regulatory barriers stricter than those found for other categories of medicines. The innovations employed in their processes are associated with high cost, due to the challenging production and technological resources used, which in turn make the biological product expensive. It is essential a standardization of requirements in quality and safety, established by the sanitary authorities to grant the marketing authorisation, to determine a balance between campaigning for health and a greater access to it. An alternative to cheapen the costs, making biological products more accessible, would be the development of biosimilars. The aim of this study is to perform a comparative analysis between the existing regulations necessary for the marketing authorisation of biological medicines in World Health Organization, the International Council on Harmonisation, the United States, the European Union and Brazil. More specifically, the objective is to explore the regulations implemented in the various regions aforementioned, and highlight the similarities and differences, advantages, weaknesses, and necessary improvements. Besides that, evaluate the impacts of substituting new biological products with their biosimilars. A comparative descriptive study, based on documentary and bibliographic research, was conducted on the proceedings and requirements of marketing authorisation of biological products adopted by the main sanitary authorities worldwide. As a result, it was found that it is necessary to update the regulation in Brazil concerned with the requirements of marketing authorisation of biological products. It is also necessary to set forth a specific regulation for registry of biosimilars and their implication related to the identity, comparability to the extension and nature of preclinical and clinical trials data to extrapolate the indications based on clinical trials. Moreover, it is important to adopt a systematic approach to evaluate the immunogenicity, including the validation of comparability assays as well as the nomenclature, labelling, automatic substitution, pharmacovigilance and interchangeability. The reinforcement of the regulatory framework of biological products, especially of biosimilars, with well-established criteria will favor the technological development of companies and increase competitiveness between them. In turn, it is expected to reduce the prices of biological products, hence allowing wider access of the population to the healthcare and sustainability of the health system.